A comparative study of efficacy of letrozole and clomiphene citrate for ovulation induction - Jain, Shaveta; Dahiya, Pushpa; Yadav, Jyoti; Jain, Nitin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study was conducted to evaluate the efficacy of letrozole as an ovulation inducing agent and to compare it with clomiphene citrate (CC) in infertile women. Methods: This study includes 100 women referred to gynecology OPD of Pt. B.D Sharma, PGIMS, Rohtak with infertility due to dysovulation. The patients were divided in two groups each comprised of 50 patients, Alternate women were enrolled in study group (Letrozole). Ultrasonic follicular monitoring was done on day 10, 12, 14, 16 of menstrual cycle to measure the number, size of mature follicles. Endometrial thickness and trilaminar pattern of endometrium was compared in between the groups. Inj. Gonadotrophin (hCG) was given as a trigger intramuscularly when follicle size was between 18 to 21mm. After 36 hours of hCG administration ovulation was confirmed on ultrasound. Results: Mean age, parity, and the duration of infertility were similar in both groups. Ovulation rate was 81.6% in letrozole group and was higher than control group(p<.01). The average number of follicles in the control group was 1.90±0.77and 1.17±0.47 in the study group(p<.001). Endometrial thickness in the study group was 7.55±1.12mm and in the control group it was 6.06±0.87(p<.01). Pregnancy rate in study group was 48 % and control group 16%(p<.05). Conclusions: Aromatase inhibitors (Letrozole) is a new group of drugs to join the arsenal of infertility treatments. The result of this preliminary study suggests that letrozole is associated with higher ovulation rate, higher endometrial thickness and trilaminar pattern thus resulting in higher pregnancy rate. Clomiphene citrate may be replaced by letrozole as primary treatment for ovulation induction in infertile patients.